PERKEMBANGAN KOGNITIF ANAK USIA DINI MELALUI PERMAINAN MENCARI HURUF - Retnaningrum, Wulandari; Umam, Nasrul (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2021)
Researchers conducted research at RA Ma'arif NU 04 Istiqomah Kalisabuk village group A. This study aims to improve cognitive development of group A children related to understanding letters. This study uses a qualitative method with a descriptive approach. The stages of the researcher in carrying out research include preparation, implementation and data processing. The data collection techniques used in the study were interviews, observation and document study using interview guidelines and observation guidelines as tools. The results of the study by reducing qualitative data found that 1) cognitive development is important at the golden age level because it occurs in the first five years of a child's life. So the process of cognitive learning activities is very important and effectively applied by playing activities; 2) early childhood cognitive development is in the pre-operational period so that they cannot think abstractly. In learning activities carried out by playing and require media; 3) through the playing method to look for letters using letter cards media, giving questions to children while doing activities. With this method children learn to recognize and understand letters.